Dynamic co-movement and spillover between the stock market and the foreign exchange market in ASEAN-5 - Te, Kai Shuan (2022)
The trade openness and lower barrier for the capital flows have increased the interdependence between the stock market and the foreign exchange market. This study examines the co-movement between the markets in ASEAN-5 member countries (Malaysia, the Philippines, Indonesia, Singapore, and Thailand) from January 1, 2017, to July 31, 2021, with the study period covered the COVID-19 pandemic. Hence, this study attempts to analyse the direction of risk transfer and the co-movement between the markets in different investment horizons during the COVID-19 pandemic.